EFFEKTIVITAS LOGOTERAPI TERHADAP STRES PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Sri Burhani Putri ((IJP) Indonesia Jurnal Perawat, 2018)
Background : Chemotherapy is the treatment most often carried out by breast cancer patients with psychological side effects are stress. Logotherapy is one therapy that can be used as a stress management for cancer patients. Methode : The design of this study was quasi-experimental pre-post with control group with the aim of seeing changes in stress conditions before and after being given logotherapy while comparing the stress conditions of two groups of breast cancer patients undergoing chemotherapy between the intervention group (given logotherapy) and the control group (not given logotherapy. Data collection was carried out using the Depression Anxiety and Stress Scale (DASS) instrument and the University of Indonesia Mental Health Nursing Therapy Module. Result : The results showed the characteristics of breast cancer patients undergoing chemotherapy at the Dr. M. Djamil General Hospital, Padang, among others, mostly over 45 years of age. bersuku minang, married status, long since diagnosis of cancer less than 2 years, stage 3 and long time undergoing chemotherapy less than 3 years and experiencing moderate stress levels and statistical test obtained a value of 0,000. Conclusion : There is a significant difference between stress levels of breast cancer patients undergoing chemotherapy in RSUP DR. M. Djamil Padang before and after logotherapy intervention.Keywords : stress, chemotherapy, logotherapy